Induction of the transcription factor Sp1 during human cytomegalovirus infection mediates upregulation of the p65 and p105/p50 NF-kappaB promoters. - Yurochko, A D (1997)
During human cytomegalovirus (HCMV) infection, the promoters for the classical NF-kappaB subunits (p65 and p105/p50) are transactivated. Previously, we demonstrated that the viral immediate-early (IE) proteins (IE1-72, IE2-55, and IE2-86) were involved in this upregulation. These viral factors alone, however, could not account for the entirety of the increased levels of transcription. Because one of the hallmarks of HCMV infection is the induction of cellular transcription factors, we hypothesized that one or more of these induced factors was also critical to the regulation of NF-kappaB during infection. Sp1 was one such factor that might be involved because p65 promoter activity was upregulated by Sp1 and both of the NF-kappaB subunit promoters are GC rich and contain Sp1 binding sites. Therefore, to detail the role that Sp1 plays in the regulation of NF-kappaB during infection, we initially examined Sp1 levels for changes during infection. HCMV infection resulted in increased Sp1 mRNA expression, protein levels, and DNA binding activity. Because both promoters were transactivated by Sp1, we reasoned that the upregulation of Sp1 played a role in p65 and p105/p50 promoter activity during infection. To address the specific role of Sp1 in p65 and p105/p50 promoter transactivation by HCMV, we mutated both promoters. These results demonstrated that the Sp1-specific DNA binding sites were involved in the virus-mediated transactivation. Last, to further dissect the role of HCMV in the Sp1-mediated induction of NF-kappaB, we examined the role that the viral IE genes played in Sp1 regulation. The IE gene products (IE1-72, IE2-55, and IE2-86) cooperated with Sp1 to increase promoter transactivation and physically interacted with Sp1. In addition, the IE2-86 product increased Sp1 DNA binding by possibly freeing up inactive Sp1. These data supported our hypothesis that Sp1 was involved in the upregulation of NF-kappaB during HCMV infection through the Sp1 binding sites in the p65 and p105/p50 promoters and additionally demonstrated a potential viral mechanism that might be responsible for the upregulation of Sp1 activity.